Battle of Wagram in 1809 - Aubert, Pierre-Eugène (engraver):::Creator::::::::::::; Bellangé, Hippolyte, 1800-1866 (artist) ; Gavard, Charles, b1794:::Contributor:::::::::::: (Gavard)
Engraving of the Battle of Wagram in 1809